1991
DOI: 10.1080/02772249109357761
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated diphenyl ethers—A review

Abstract: Polychlorinated diphenyl ethers (PCDEs) have been identified as by-products formed in the synthesis of chlorinated phenols. Analytical surveys have shown that PCDE residues are present in sediments, fish, wildlife, and human tissues. The uptake and persistence of PCDEs in laboratory animals resembled that observed for the polychlorinated biphenyls (PCBs), however, in metabolic studies, ortho hydroxylation of the PCDEs was the dominant oxidative pathway. Studies indicate that PCDE congeners elicit a broad spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…PCDEs are becoming of great concern because of their structural and toxicological similarity to polychlorinated biphenyls (Becker et al 1991). Studies indicate that PCDE congeners show a broad spectrum of toxic and biochemical responses in laboratory animals, including the induction of cytochrome P-450-dependent mono-oxygenase enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…PCDEs are becoming of great concern because of their structural and toxicological similarity to polychlorinated biphenyls (Becker et al 1991). Studies indicate that PCDE congeners show a broad spectrum of toxic and biochemical responses in laboratory animals, including the induction of cytochrome P-450-dependent mono-oxygenase enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Industrially, DEs are finding increased uses as components of heat transfer media, as solvents, and in plasticizers (Francis, 1986). Polychlorinated DEs are manufactured for use as flame retardants and herbicides (Becker et al, 1991). Due to the marked toxicity of several congeners of the halogenated diaryl ethers and their general resistance to degradation, because of their physical, chemical, and biological stabilities (Hoffman et al, 1991), the study of mechanisms whereby such compounds may be degraded are of interest.…”
Section: Microbial Degradation Of De and 3-or 4-carboxy Dementioning
confidence: 99%
“…Similar to their analogues, PCDEs with lipophilic and persistent properties tend to bioaccumulate and biomagnify in food webs (Domingo, 2006). Some PCDEs may have biochemical and toxic effects similar to those of PCBs and PCDD/Fs (Becker et al, 1991). Furthermore, PCDEs may be converted to or form toxic PCDD/Fs by photolysis or pyrolysis (Norström et al, 1976;Lindahl et al, 1980;Liu et al, 2010), and have been observed in the flue gas and fly ash of waste incinerators (Kurz and Ballschmiter, 1995;Nakao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%